Respon Genotipe Padi Sawah terhadap Pemupukan Nitrogen Di Dataran Tinggi (Response of Rice Genotypes to Nitrogen Fertilizer in Highland) - Yusuf La’lang Limbongan; Bambang Sapta Purwoko; , Trikoesoemaningtyas; Hajrial Aswidinnoor (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
The objective of this experiment was to study the response of rice genotypes to nitrogen under low temperature stress condition.  This experiment was done at Sesean rural area, Tana Toraja Regency, South Sulawesi, 1500 m above sea level with mean temperature 18oC. Experiment was designed in Completely Randomized Block Design with two factors.  The first factor comprised of 3 levels of Nitrogen dosage (0, 50, and 100 kg N / ha) and the second factor was cultivar i.e. Pulu' Mandoti, Pinjan, Lambau, Fatmawati, Sintanur and Gilirang.  The results showed that at low temperature stress condition, nitrogen, cultivar and their interaction gave significant effect on percentage of pollen fertility, percentage of filled spikelet and weight of filled grain per spikelet, while interaction between nitrogen and cultivar did not significantly affect the flag leaf length and flowering date. Rice yield decreased with increasing N levels under low temperature stress condition. There were significant positive correlations between growth components (percentage of pollen fertility, flag leaf length and flowering date) and yield components (number of tiller and grain per panicle and weight of 1000 grain).   Key words:  low temperature stress,  nitrogen fertilizer, rice, highland, pollen fertility